FAKTOR – FAKTOR YANG MEMPENGARUHI IMPLEMENTASI BADAN JALAN UMUM SEBAGAI OBJEK PENERIMAAN RETRIBUSI PARKIR DI KOTA PEKANBARU - Ardina, Zenni; ", Sujianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The using of public road as the parking facilities is implemented to arrange the parking and to increase the local own source revenue of Pekanbaru city. However, the income of parking retribution in Pekanbaru was not stable because of the increasing and decreasing of using the public road, and then did not success to achieve the target. The parking retribution’s target that determined by Department of Communication and Information was still far from the parking retribution potential. An illegal parking practical was one of the problems that caused of the unstable of parking retribution’s revenue. This study aimed to know the factors affecting the implementation of public road as the object of parking retribution’s revenue in Pekanbaru city.In the theory of Edward III, there are 4 (four) implementation’s indicators, i.e. communication, resource, disposition, and bureaucratic structure. The method of descriptive qualitative with purposive sampling technique was used in this research. The interviewees of this research were Department of Communication and Information, parking coordinators, and parking service users.Based on the result of analyzing a data qualitative descriptively, factors affecting the implementation of public road as the object of the parking retribution’s revenue in Pekanbaru city was not successfully yet. An ineffectively communication between stake holders caused the problem, and the unfair effect to target of the policy was caused stake holders did not surely understand about their duties and responsibilities.Keywords : Implementation, Road, Retribution